ZBRODNICZE ZAMIARY A ISTNIENIE OBRONY KONIECZNEJ W PRAWIE RZYMSKIM - Loska, Elżbieta (Zeszyty Prawnicze, 2017)
C r i m i n a l In t e n t a n d t h e Ex i s t e n c e o f Se l f D e f e n c e i n t h e Ro m a n La w Summary In ancient Rome, initially the sanctions for a m urder applied to its perpetrator regardless his motives. The liability resulting from lex Cornelia was also based rather on the result, viz., the objective element of the act. This was true when the perpetrator’s act led to the victim’s death. In other situations provided for in the act, the perpetrator was punished only when the intent of com m itting a crime was shown. Carrying weapons was allowed only to defend oneself. In the Hadrian’s rescript issued in order to regulate a murder com m itted during an affray, the emperor ordered the judges to carefully examine the circumstances and severely punish the perpetrator but only when he acted w ith an intent of a murder. It resulted from the content of the rescript that a person who killed a man, could be released if he had not acted with an intent of committing a crime whereas a person who wounded in order to kill was to be punished as a murderer. The result of a crime was less significant than the intent. Caesar Hadrian, however, did not go into the processes undergoing in the perpetrator’ psyche that drove him to commit a crime. Therefore a new element was taken into account, namely impetus. It related to the crimes com m itted under emotions. A crime committed under impetus resulted from an uncontrolled impulse caused by an abnormal state of the perpetrator’s psyche. It seems possible to ascribe the actions taken as a self-defence to this group. The constitutions of the subsequent emperors also ordered the judges to take into account the attitude of the perpetrator in examining cases of a m urder. The releases from liability are usually connected with an objective element of a crime. In the ancient sources a different approach, which stresses the existence of the subjective element, may be also traced. Relating the self-defence release with the existence of the animus occidendi seems therefore justified.